Extreme Temperatures, Health and Retirement - Albanese, Andrea; Deschenes, Olivier; Gathmann, Christina; Nieto Castro, Adrian (Working Papers, 2025)
This paper provides novel evidence of the impact of temperature fluctuations on retirement behavior and underlying mechanisms, combining 30 years of rich longitudinal survey data with granular daily weather information. Exposure to cold and hot temperatures accelerates transitions into retirement, particularly among individuals unaccustomed to such conditions, and the effects are strongest among vulnerable populations facing greater health challenges and limited access to healthcare. Extreme temperatures deteriorate health through a higher incidence of cardiovascular diseases and strokes, reducing individuals’ ability to work, while better access to healthcare mitigates the adverse effects of extreme temperatures on retirement behavior.
Keywords: Temperature; Health; Retirement; Healthcare; I14; I18; J26; Q54